2011
DOI: 10.1007/s00784-011-0589-9
|View full text |Cite
|
Sign up to set email alerts
|

Two-body wear of dental porcelain and substructure oxide ceramics

Abstract: The aim of this in vitro study was to investigate the two-body wear of different ceramics. Two-body wear tests were performed in a chewing simulator with steatite and enamel antagonists, respectively. Specimens were loaded in a pin-on-block design with a vertical load of 50 N for 1.2 × 10(5) cycles; (f = 1.6 Hz; lateral movement, 1 mm; mouth opening: 2 mm). Human enamel was used as a reference. Three zirconia ceramics, three veneering porcelains, two glass-infiltrated and one lithium disilicate ceramic were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
5
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 30 publications
3
63
5
4
Order By: Relevance
“…3a). As opposed to findings in other laboratory studies (Jung et al, 2010;Preis et al, 2012;Rosentritt et al, 2012) the wear of enamel antagonists by feldspathic ceramic (VM) and glass ceramic (EC) was not significantly different from that of zirconium dioxide ceramics (Tab. 2).…”
Section: Two-body Wear Of Silicate and Hybrid Ceramicscontrasting
confidence: 84%
See 1 more Smart Citation
“…3a). As opposed to findings in other laboratory studies (Jung et al, 2010;Preis et al, 2012;Rosentritt et al, 2012) the wear of enamel antagonists by feldspathic ceramic (VM) and glass ceramic (EC) was not significantly different from that of zirconium dioxide ceramics (Tab. 2).…”
Section: Two-body Wear Of Silicate and Hybrid Ceramicscontrasting
confidence: 84%
“…The zero m-wear for monolithic zirconium dioxide ceramics (IN) and minimal a-wear (25.5 µm) of its enamel antagonists both impressed ( Fig.1; Table 2), even though these properties have already been reported for zirconium dioxide ceramics by recent laboratory studies (Jung et al, 2010;Preis et al, 2012;Rosentritt et al, 2012;Stawarczyk et al, 2012). The contact area of IN looked slightly polished at the end of the test, while, other than the rougher contact areas of the control facets of a-enamel against m-enamel (Fig.…”
Section: Two-body Wear Of Zirconium Dioxide Ceramicsmentioning
confidence: 87%
“…With recent developments in CAD/CAM (computeraided design/computer-assisted manufacture) technologies and with the introduction of new ceramic materials, the possibility of milling full-contour ceramic restorations without veneering has gained increasing importance and popularity. Associated with these developments of the concept that if ceramic chipping could be avoided and the wear of ceramics and antagonists could be reduced [4][5][6][7][8] , the application of the veneering porcelain has been decreasing in the clinical situation. TZP could be used for fabricating high-strength monolithic restorations 9,10) and might be indicated, especially in posterior regions.…”
Section: Introductionmentioning
confidence: 99%
“…This study was carried out using uniform conditions to test standardized antagonist specimens. In the previous studies 5,6,10,[12][13][14][15][16][17] , standardized antagonist specimens such as magnesium silicate and human enamel have been used. The current study employed standardized rounded rod specimens made of type 4 gold alloy and HP ceramics, both are applicable for centric holding cusps of premolars and molars.…”
Section: Discussionmentioning
confidence: 99%
“…Preis et al reported that polished zirconia yielded superior wear behavior and lower antagonistic wear compared to other ceramics 15) . Thus, polished zirconia tend to show lower wear on antagonists than other ceramics 5,6,10,[12][13][14][15][16][17] . There have been past studies using rounded rod specimen such as magnesium silicate and human enamel 5,6,10,[12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%